ANALISIS KELAYAKAN USAHA DODOL RUMPUT LAUT DI UD. HARKAT MAKMUR KECAMATAN CAKRANEGARA - IDA AYU NOPIARI (GANEC SWARA, 2024)
One of the processed seaweeds is in the form of seaweed dodol. People's demand for seaweed dodol is increasing. The use of seaweed for dodol products can provide added value to the food. It is necessary to process seaweed products considering the high nutritional content in them. Therefore, dodol is a favorite food and is quite popular in several regions of Indonesia, including Lombok. Based on the above, research was conducted with the title "Feasibility Analysis of the UD Seaweed Dodol Business. Harkat Makmur” Cakranegara District. The aim of this research is: to analyze the feasibility of seaweed dodol processing business at UD. Harkat Makmur is based on Benefit Cost (B/C) Ratio, Revenue Cost (R/C) Ratio, and Break Even Point (BEP).               Based on the results and discussion of research results, it can be concluded that UD Harkat Makmur's seaweed dodol business was declared feasible because it had a B/C ratio value of 3.42 > 1. The B/C ratio value of 3.42 shows that for every Rp. 10,000 spent by UD Harkat Makmur it is estimated that it will make an average profit. -an average of IDR 34,200.